2015
DOI: 10.4314/jab.v90i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and phytochemical screening of Endophytic fungi from stems of <i>Phragmanthera capitata</i> (Sprengel) S. Balle (<i>Loranthaceae</i>)

Abstract: Objective: The purpose of this study was to identify some endophytic fungi, which were associated with the stems of Phragmanthera capitata (Loranthaceae), and to determine the phytochemical composition of their extracts. Methodology and results:The isolation of endophytic fungi was made on PDA medium (Potato dextrose agar) and the identification was based on macroscopic and microscopic observations of the different strains isolated and using identification keys. The qualitative phytochemical analysis of acetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The characteristics of the bactericidal and fungicidal effect of Ag NPs are dependent upon a number of properties, including particles size and size distribution, solubility and state of aggregation, elemental composition, mass and concentration, shape and crystal structure, surface area, charge, chemistry and the presence of impurities8586. In the previous studies the superiority of the positively charged Ag NPs over the negatively charged particles, in terms of the antibacterial activity, was demonstrated882. The role of surface charge in their bacterial activity was assessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the bactericidal and fungicidal effect of Ag NPs are dependent upon a number of properties, including particles size and size distribution, solubility and state of aggregation, elemental composition, mass and concentration, shape and crystal structure, surface area, charge, chemistry and the presence of impurities8586. In the previous studies the superiority of the positively charged Ag NPs over the negatively charged particles, in terms of the antibacterial activity, was demonstrated882. The role of surface charge in their bacterial activity was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Chemicals prospecting in ethyl acetate extracts of both fungal cell-free supernatant were performed to observe the presence of the following secondary metabolites: alkaloids, flavonoids, tannins, phenols, steroids, saponins, terpenoids and cardiac glycosides by using standard procedures as described by843444546474849.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study in Phragmanthera capitata 11 endophytic fungi species from four genera: Aspergillus (six species), Penicillium (three species), Trichoderma (one species) and Fusarium (one species). In the same study the phytochemical analysis revealed the presence of flavonoids, anthroquinones, tannins, phenols, steroids, coumarins and terpenoids, and absence of alkaloids and saponins in all the extracts (Ladoh-Yemeda et al, 2015). Micromorphological studies of the Loranthaceae P. capitata with scanning electron, light, and energy dispersive X-ray (EDX) microscopies revealed a paracytic type of stomata, oval-shaped lenticels, densely packed stellate trichomes, tracheary elements, which are tightly packed with granules believed to be proteins, and deposits chiefly composed of Si, Al, K, and Fe (Ohikhena et al, 2017).…”
Section: Introductionmentioning
confidence: 68%
“…Likewise, preliminary phytochemical screening of the methanolic extracts of H. elastica in hosts, N. indicum and H. brasiliensis, revealed the occurrence of various constituents as alkaloids, glycosides, flavonoids, phenols, tannins, sterols, triterpenoids, diterpenes and carbohydrates, but not proteins or amino acids (Kumar & Mathew, 2014). In another study, phytochemical analysis of endophytic fungi from stems of Phragmanthera capitata, harvested in Theobroma cacao L., revealed the presence of flavonoids, anthroquinones, tannins, phenols, steroids, coumarins and terpenoids, but absence of alkaloids and saponins, in all acetate ethyl extracts (Ladoh-Yemeda et al, 2015). Phytochemical constituents from L. elasticus presented in the Neem Tree (A. indica), namely alkaloids, amino acids, anthocyanin, carbohydrates, cardiac glycosides, coumarins, diterpenes, emodins, fatty acids, phlobatannin, phenols, saponin and terpenoids, were presented in methanolyc extract, whereas the flavonoids, glycosides, leucoanthocyanin, phytosterol, proteins, steroids and tannin were absent in methanol extract.…”
Section: Discussionmentioning
confidence: 96%